Cauliflower-Like Appearance of Calcified Nodules Observed by Coronary Angioscopy. (September 2017) - Dai, Kazuoki; Suruga, Kazuki; Nakao, Yasuhisa; Kobayashi, Yusuke; Ikegami, Yuki; Takemoto, Hajime; Higaki, Tadanao; Oi, Kuniomi; Kawase, Tomoharu; Nakama, Yasuharu; Suenari, Kazuyoshi; Nishioka, Kenji; et al.
Abstract : Supplemental Digital Content is available in the text.